Attitude towards future elderly support: a study among Indonesian young adults - Setiyani, Rahmi; Sumarwati, Made; Ramawati, Dian (International Journal of Research in Medical Sciences, 2017)
Background: Demographic phenomenon of population ageing in Indonesia has raised concern over number of issues including the provision of long-term support for older people. Since young generation has been influenced by social economic development, this may affect the willingness of taking care for their ageing parents. This study is intended to examine adult children’s willingness to parent care in the future and factors that associated with. Methods: This cross sectional study was conducted among well-educated young adults who have a potential conflict between work responsibility and obligation to care for elderly parent in the future. A total of 300 final year students of a state university in Purwokerto district, Central Java, Indonesia, participated in this study. A self-administered questionnaire, using Likert scale (1-4), was used to measure attitudes in four types of support. A higher score meant a higher willingness to provide supports. Results:The highest score was noted in emotional supports (3.67), followed by appraisal, instrumental and informational supports (3.50, 3.33 and 3.25 respectively). Gender and number of children in the family were significantly associated with commitment to provide support. Daughter showed higher willingness to provide emotional supports than son. Meanwhile, lower instrumental, appraisal and total supports were demonstrated by adult children who have one or less sibling than those who have two or more siblings. Conclusions:The findings suggest that Indonesian young adult is likely to continue to uphold the value of intergenerational support. The findings also indicate that the gendered nature of care remains unchanged.